Investigation on physical properties of patia clay (Chittagong), Bangladesh (Bangladesh Journal of Scientific and Industrial Research, 2015)
The physical and microstructural characteristics of Patia clay of different areas (Hydgaon-1, Hydgaon-2 and Kanchannagar) were investigated. Patia clays were beneficiated by repeated sedimentation method. The chemical compositions of raw (unwashed) and washed clay was determined. The physical properties of fired Patia clay were measured. Results show that the water absorption values decrease and the firing shrinkage values increase with increasing firing temperatures in all types of Patia clays (raw and washed) of three different areas. The microstructures of Patia clay pronounce that they contain kaolinite, illite and quartz as major phases and mica, gibbsite and hematite are present as minor phases. DOI: http://dx.doi.org/10.3329/bjsir.v49i4.22629 Bangladesh J. Sci. Ind. Res. 49(4), 255-262, 2014